Peripheral T-Cell Lymphomas of the T Follicular Helper Type: Clinical, Pathological, and Genetic Attributes - Karthik A. Ganapathi; Kristin H. Karner; Madhu P. Menon (Hemato, 2022)
Follicular helper T-cell (TFH) lymphomas comprise a unique group of T-cell lymphomas that represent neoplastic proliferations of follicular helper T-cells and share genetic, immunophenotypic, morphologic, and clinical features. Angioimmunoblastic T-cell lymphoma (AITL) is the prototypical TFH lymphoma; in addition, the 2017 revised World Health Organization (WHO) 4th edition recognizes two other unique subtypes: follicular T-cell lymphoma (FTCL) and nodal peripheral T-cell lymphoma with the T follicular helper phenotype (PTCL-TFH). This review discusses the morphologic spectrum, immunophenotype, diagnostic mimics/pitfalls, and unique genetic attributes of this category of T-cell lymphomas.